Adverse effects of modern communication technologies on the Serbian elementary and secondary school pupils in Niš region - Jevtić, Radoje B.; Janković, Ivana; Lukić, Jelena (Education and Research in Health Sciences, 2025)
Introduction/Objective: This longitudinal research had three aims. The first aim was to show the influence of different devices in the life and work of elementary and secondary school pupils, their relationship and rationality about those devices, and their exposure to those devices. The second aim was to show the behaviour on the Internet as a prerequisite for exposure to digital violence for pupils. The third aim was to show the presence of digital violence among pupils. Methods: The survey method on a population of 1,500 respondents over four years, 2021, 2022, 2023, and 2024 (750 pupils from elementary schools and 750 pupils from secondary schools in Niš) was used. Also, in the calculation of results, statistical and mathematical methods were used. Results: The obtained results showed that pupils use modern digital devices in their life and work significantly, especially mobile phones (every pupil had a mobile phone). The exposure to digital violence among respondents was very high (every pupil uses some kind of social network). Digital violence exists among respondents in a high degree (pupils were harassed by e-mail, phone, or social networks with different percentages, from 30% to 90%). Conclusion: Modern digital devices are widely used among school-age children, which directly implies increased quantities of electromagnetic radiation and exposure to digital violence. Digital violence presents a serious and increasing problem in the modern society, as a direct consequence of the usage of digital devices and social networks and therefore must be stopped and eliminated in the best possible way.